Multicultural Education in Developing Islamic Education Teaching Materials on Students' Tolerant Attitudes in Elementary Schools - Masbur; Syahril (MANDAILING GLOBAL EDUKASIA, 2024)
This article aims to provide an overview of Multicultural Education in developing Islamic education Teaching Materials towards Students' Attitudes of Tolerance. The research method used is research in the form of a library study as a step in solving a problem by carefully and intensely reviewing relevant library data. The sources of library data in question are books, scientific articles and journals. The approach is descriptive qualitative, where the use of data is taken qualitatively and described or explained descriptively. Data processing to produce information is obtained through several processes including the process of searching for data, the process of collecting data, the process of processing/analyzing data, and the process of concluding data. The research results found that Islamic education learning through multicultural education ensures that students are not only able to understand and master the subject matter they study. In this case, what a teacher needs to do is form a Islamic education learning pattern through activities in the classroom; be universal and not discriminate between students; and inserting tolerance values in teaching materials.